Growth and characterization of α-, β-, and ϵ-phases of Ga2O3 using MOCVD and HVPE techniques - Yao Yao; Serdal Okur; Luke A. M. Lyle; Gary S. Tompa; Tom Salagaj; Nick Sbrockey; Robert F. Davis; Lisa M. Porter (Materials Research Letters, 2018)
Heteroepitaxial films of Ga $ _2 $ O $ _3 $ were grown on c-plane sapphire (0001). The stable phase β-Ga $ _2 $ O $ _3 $ was grown using the metalorganic chemical vapor deposition technique, regardless of precursor flow rates, at temperatures between 500 $ ^\circ $ C and 850 $ ^\circ $ C. Metastable α- and ϵ-phases were grown when using the halide vapor phase epitaxy (HVPE) technique, at growth temperatures between 650 $ ^\circ $ C and 850 $ ^\circ $ C, both separately and in combination. XTEM revealed the better lattice-matched α-phase growing semi-coherently on the substrate, followed by ϵ-Ga $ _2 $ O $ _3 $ . The epitaxial relationship was determined to be [ $ \bar {1}100 $ ] ϵ-Ga $ _2 $ O $ _3 $ $ \| $ [ $ 11\bar {2}0 $ ] α-Ga $ _2 $ O $ _3 $ $ \| $ [ $ 11\bar {2}0 $ ] α-Al $ _2 $ O $ _3 $ . SIMS revealed that epilayers forming the ϵ-phase contain higher concentrations of Cl introduced during HVPE growth.